Aid Methods of Treatment in the Recovery Period of Patients Underwent Surgical Treatment of Cervical Hip Fractures (Literature Review) - Oleg N. Yamshchikov; Sergey A. Emelyanov; Sergey A. Mordovin; Anton N. Petrukhin; Ekaterina A. Kolobova; Eldar A. Greznev; Roman S. Manyakhin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
The literature review summarizes the scientific information devoted to the study of auxiliary methods used in restorative treatment after surgery for fractures of the femoral neck. The restoration of motor functions in patients with cervical hip fractures is a priority task of the comprehensive restorative treatment program. Despite the achievements in the field of osteosynthesis and endoprosthetics, many patients receive an unfavorable outcome of surgery and a group of disabilities. As a result of an improperly selected program of complex rehabilitation treatment or neglect of auxiliary methods, in most cases, patients gradually develop secondary complications from the damaged segment: the formation of articular contractures, muscle hypo- and atrophy, violation of the walking stereotype, ineffective consolidation, fracture and migration of metal structures with excessive load on the limb, etc., as well as the general somatic condition of the patient worsens: secondary hypostatic complications join and chronic diseases a exacerbated. The purpose of the literature review is to systematize data on the use of auxiliary treatment methods in the recovery period of patients who have undergone surgical treatment of hip fractures and their effectiveness. The article discusses the general characteristics of the applied auxiliary methods of restorative treatment, the timing and scope of their implementation, and also presents the results of individual randomized controlled trials on their effectiveness.